Examining Digital Brand Experiences as a Predictor of Brand Relationship Quality and Loyalty - Orhan, Mehmet A. (2020)
Experiences are getting increasingly common in digital platforms. Yet, there is a scant explanation of the impact of digital experiences on consumer behavior. The aim of this paper is to examine the quality of brand relations and brand experiences on satisfaction and loyalty of digital experiences in a new era of experience economy. A quantitative study is designed to explore the brand loyalty and brand satisfaction in association to brand relationship quality and brand experiences in digital worlds. Based on the responses of 154 people, mainly residing in the US, we found positive impacts of perceived brand relationship quality and brand experiences on brand satisfaction and loyalty. Our paper emphasizes the influence of perceived brand identity notion in digital experiences. By designing a blueprint for marketing experiences, companies can develop innovative processes to deliver more excellent experiential marketing to consumers on top of the existing features of their brand offers.